Implicit Arguments in English and Rutooro: A Contrastive Study - Isingoma, Bebwa (Linguistik Online, 2020)
The present study is a contrastive analysis of the syntactic behavior of verbs that are ontologically specified for objects but these objects may be left out without rendering sentences ungrammatical. The study unveils asymmetries between English and Rutooro (a Bantu language spoken in Uganda) in the (non-)omissibility of postverbal arguments, stemming from lexico-semantic and morphological factors as well as syntactic and discoursal factors. In light of the asymmetries arising from syntactic and discoursal factors, the study adopts a typology of indefinite implicit arguments that categorizes them into two: general indefinite implicit arguments and discourse-bound indefinite implicit arguments. Denotational nuances between synonyms as well as morphological specifications are also crucial linguistic ingredients that trigger variability in the syntactic behavior of synonymous verbs intralinguistically and cross-linguistically. In order to formalize the syntactic behavior of the verbs involved, the study employs the analytical tools provided by Lexical Functional Grammar (LFG). While Asudeh/Giorgolio (2012) use a combination of LFG and Glue Semantics in order to account for the occurrence of implicit arguments, this study proposes an alternative approach, by using only the LFG functional specifications in the lexical entries of the verbs under consideration without having recourse to an auxiliary framework. Using Bresnan (1978) as a point of departure and informed by proposals advanced by Nordlinger/Sadler (2007), the study posits a non-ambiguous bistructural analysis, with the postverbal argument instantiating the specification ± higher structure – a feature that caters for the (non-)omissibility of the postverbal argument.